Methanol as the C1 source: redox coupling of nitrobenzenes and alcohols for the synthesis of benzimidazoles. Issue 2 (14th December 2021) - Li, Hengzhao; Zhang, Yuntong; Yan, Zihan; Lai, Zemin; Yang, Ruoyan; Peng, Mengqi; Sun, Yanhao; An, Jie
Abstract : We present a greener redox coupling reaction for the synthesis of benzimidazoles using methanol as the C1 source. Abstract : We present an operationally simple redox coupling for the synthesis of N-1 substituted benzimidazoles using feedstock building block 2-nitroaniline derivatives as the precursors and methanol as the C1 source. Higher atom, step, and redox economies and excellent regioselectivity were achieved compared with conventional synthesis using diaminobenzene and formic acid derivatives.